ANALISIS PENENTUAN PUSAT-PUSAT PERTUMBUHAN EKONOMI DI KABUPATEN SIMALUNGUN - Pandapotan Nainggolan (Ekonomi dan Keuangan, 2013)
The purpose of this study is to determine districts as growth center inKabupaten Simalungun and to determine the relationship between the growth center with its hinterland. The method of analysis used was analysisScallogram with Centrality Index and analysis of Gravity.The results of analysis scalogram with centrality index obtained district thatbecame as centers of growth are Kecamatan Siantar, Bandar, Tanah Jawa,Raya dan Bosar Maligas. While the analysis of gravity obtained interactionthe growth centers with its hinterland. The growth center Siantar have themost interaction with Gunung Malela, Bandar have the most interaction withPematang Bandar,  Kecamatan Tanah Jawa have the most interaction withHatonduhan, Kecamatan Raya have the most interaction with Panei andKecamatan Bosar Maligas have the most interaction with Bandar. Keywords : Growth Center, Scallogram, Centrality Index, Gravity